2018
DOI: 10.1016/j.puhe.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of occupational safety and health training for migrant farmworkers: a scoping review

Abstract: Training could greatly contribute to an effective attainment of OSH information, but the present review shows that more evidence is needed to guide the future development of effective training activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
(106 reference statements)
1
18
0
Order By: Relevance
“…Education has been acknowledged as the most powerful transformative force in the achievement of a sustainable future (Hopkins & McKeown, ). Education requires a participatory approach in teaching and in the development of training methods (Caffaro, Micheletti Cremasco, Bagagiolo, Vigoroso, & Cavallo, ) to motivate and empower both apprentices and teachers to learn, reflect, change their behavior, and take action for sustainable development. The participation of stakeholders is deeply rooted in the vision of sustainable development as a collaborative process of involving stakeholders to initiate and diffuse the technical, organizational, and social innovations necessary for greater sustainable development, with regard to environmental, social, and economic aspects (Moss & Fichter, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education has been acknowledged as the most powerful transformative force in the achievement of a sustainable future (Hopkins & McKeown, ). Education requires a participatory approach in teaching and in the development of training methods (Caffaro, Micheletti Cremasco, Bagagiolo, Vigoroso, & Cavallo, ) to motivate and empower both apprentices and teachers to learn, reflect, change their behavior, and take action for sustainable development. The participation of stakeholders is deeply rooted in the vision of sustainable development as a collaborative process of involving stakeholders to initiate and diffuse the technical, organizational, and social innovations necessary for greater sustainable development, with regard to environmental, social, and economic aspects (Moss & Fichter, ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Rogers (1976), the topic of control is strictly interwoven with the concept of development, which can be defined as " Education has been acknowledged as the most powerful transformative force in the achievement of a sustainable future (Hopkins & McKeown, 2001). Education requires a participatory approach in teaching and in the development of training methods (Caffaro, Micheletti Cremasco, Bagagiolo, Vigoroso, & Cavallo, 2018) to motivate and empower both apprentices and teachers to learn, reflect, change their behavior, and take action for sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the theoretical basis for the intervention, 11 articles mentioned behavioral theories such as the Theory of Reasoned Action [51], the Theory of Planned Behavior [61], the Diffusion of Knowledge Theory [56,59], the Trans-Theoretical Model [53], the Health Belief Model [54,62,63], the conceptual model for Community-Based Participatory Research [55,59,63,64], or the conceptual framework developed by WHO [58]. Four articles [22,24,29,31] did not mention any evidence-based theory for the development of the interventions. The concept of health literacy was not mentioned in any of the studies, but (general) literacy was mentioned in seven of them [50][51][52][53][54]56,57], two of which tied literacy with health education and reducing poisonings from pesticide handling [56,57].…”
Section: Studies Focusing On Accident and Injury Preventionmentioning
confidence: 99%
“…Among the farming population, there are specific types of workers, such as migrants, who are often employed in agriculture [22] and as such are exposed to occupational hazards and risks [23]. Low levels of education, diversity of language, young age and lack of experience are characteristics that differentiate the specific needs in terms of agricultural training and approaches to health safety training for this type of agricultural worker [24,25]. Apart from migrants, there are other populations that are affected by agriculture hazards, such as women and youth.…”
mentioning
confidence: 99%
“…Caffaro and colleagues conducted a literature review on occupational safety and health training programs addressing migrant farmworkers, including animal workers, to determine the effectiveness of the standard programs in place [68]. The majority of the reviewed studies found the training programs to be ineffective, with no or little difference in injury outcomes with or without the standard training programs.…”
Section: Occupational Injurymentioning
confidence: 99%